Diversity and Abundance of Carabidae and Staphylinidae (Insecta: Coleoptera) in Four Montane Habitat Types on Mt. Bawakaraeng, South Sulawesi - Agmal Qodri; Rika Raffiudin; Woro Anggraitoningsih Noerdjito (Bogor Agricultural University, Indonesia, 2016)
Carabidae and Staphylinidae are the two beetle families frequently found to be most abundant and diverse in forest ecosystem. Their roles especially as generalist predators are important in forest ecosystem. No studies reported their diversity and abundance in forest ecosystem on Mt. Bawakaraeng, specifically in montane habitat yet. This study was aimed to analyze diversity and abundance of Carabidae and Staphylinidae in four montane habitat types, i.e. agricultural area, pine forest, eucalypts and natural forest (1,835 m asl), and natural forest (2,165 m asl). They were collected using pitfall traps. A total of 42 carabid beetles belonging to nine species and 260 staphylinid beetles belonging to 37 species were collected. Diversity and abundance of Staphylinidae were higher than Carabidae, this is predicted because of higher mobility in Staphylinidae compared to Carabidae. In Carabidae, the highest species richness was recorded in agricultural area, whereas the highest species richness of Staphylinidae occurred in natural forest (2165 m asl). In Staphylinidae, the two largest subfamilies are Aleocharinae and Staphylininae. Aephinidius adelioides occupied the highest abundance of Carabidae and found in agricultural area. The differences in each montane habitat type are presumed to cause variation in species richness of soil beetles, especially for Carabidae.